"Your Head is on the Chopping Block": Exploring the Transitions from Primary Trainee Teacher to Early Career Teacher in England - Coverdale, Louise; Glazzard, Jonathan (International Journal of Educational and Life Transitions, 2024)
This paper is based on the first author’s doctoral research. Existing literature demonstrates that teachers experience high workloads, significant accountability, poor mental health, burnout and low job satisfaction. Longitudinal studies which explore pre-service teachers’ experiences of their initial teacher training and then subsequently their transitions into, and through, their first year of teaching are rare, and therefore this study addresses a significant gap in knowledge. This study explored participants’ experiences of transitions during their initial teacher training year and first year of teaching. The study adopted a longitudinal design and data were captured at key points during the training year and first year of teaching. Data were captured using a focus group, semi-structured interviews, photo-elicitation, and diaries. The data indicate that participants experienced multiple and multi-dimensional transitions as they progressed in their careers from pre-service teacher to early career teacher. These include physical, social, cultural, and psychological transitions. These transitions also impacted on others, thus illustrating the multi-dimensional nature of transitions. Implications for theory and practice are drawn out of the data. We offer a modified framework to support the development of teachers at the early stages of their careers.
Keywords: Early career teacher; transitions; pre-service teacher; teaching; education